Scalable Non-injection Synthesis of Cd-Free Copper Indium Sulfide/Zinc Sulfide Quantum Dots for Third-Gen Photovoltaic Application. Issue 30 (28th July 2016) - Zheng, Yaxin; Sadeghimakki, Bahareh; Jahed, Navid. M. S.; Sivoththaman, Siva
ABSTRACT: Copper Indium Sulfide (CIS)-based quantum dots (QDs) are considered as a safer alternative compared to carcinogenic cadmium- and lead-based QDs. Here, we present a facile, high throughput, and non-injection method of synthesizing CIS-based QDs. The structure, shape, size, and crystalline structure of the synthesized QDs were studied using high resolution transmission electron microscopy (HRTEM). The effects of temperature and compositional dependency on the structure and optical properties of the resulting QDs were investigated using elemental, absorption, photoluminescence (PL), and time-resolved spectroscopic analyses. We observed that a gradient increase of temperature during the core growth, as well as addition of excess indium (In) and zinc (Zn) precursors during core and core/shell synthesis, at low growth temperatures, resulted in QDs with improved PL and lifetime. The large Stokes shift, broad emission spectra, and long-lived emission of the synthesized QDs reveal their potential applicability to third generation photovoltaic and optoelectronic devices.